(untitled) (Ukrainian Journal of Ophthalmology, 2026)
The aim of the research is the analysis of text visual load influence on the structural and functional state of children’s and teenagers’ visual system. 97 children and teenagers as well as 88 young adults took part in the research. Materials and methods. The research has been carried out with the participation of 97 children and teenagers and 88 young adults. The texts with different typographic parameters on the paper carrier were used as a visual load. The typestyle of 10 typographical points was used for normal texts and 7 typographic points typestyle was used for the texts with undersized parameters. The positive reserve of accommodation for distance, the near point of clear vision and convergence were used for estimation of visual system state in the dynamics of visual work. Results. The factor analysis allowed establishing that the special mechanisms of visual perception of close objects were not formed in children and teenagers. It was proved by the fact that the visual work at close distance had led to obvious visual system stress. This stress was manifested by the increase in significant connections in the visual system and by presence of random components. Several different types of system organization have been determined at the same time. The configuration and number of connections in the visual system of young adults was preserved after the visual load. This is evidence that the visual system formation is completed in adult persons.